1998
DOI: 10.1016/s0550-3213(98)00287-9
|View full text |Cite
|
Sign up to set email alerts
|

Radiative corrections to W+W− → W+W− in the electroweak standard model

Abstract: The cross-section for W + W − → W + W − with arbitrarily polarized W bosons is calculated within the Electroweak Standard Model including the complete virtual and softphotonic O(α) corrections. We show the numerical importance of the radiative corrections for the dominating polarized cross-sections and for the unpolarized cross-section. The numerical accuracy of the equivalence theorem is investigated in O(α) by comparing the cross-section for purely longitudinal W bosons obtained from the equivalence theorem … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 56 publications
3
55
0
Order By: Relevance
“…The authors of Ref. [61], for example, have shown that unitarity-breaking terms can show up in the final form for the amplitude. From a formal perspective, indeed, transition amplitudes have to be defined in terms of asymptotic states containing stable particles only.…”
Section: Higgs-boson Mass and Wave-function Renormalizationmentioning
confidence: 99%
“…The authors of Ref. [61], for example, have shown that unitarity-breaking terms can show up in the final form for the amplitude. From a formal perspective, indeed, transition amplitudes have to be defined in terms of asymptotic states containing stable particles only.…”
Section: Higgs-boson Mass and Wave-function Renormalizationmentioning
confidence: 99%
“…Moreover very subtle gauge cancellations take place especially as the energy of the participating W 's increases. The most complete calculation has been performed in [163] and the code is freely available at www.hep-processes.de. However, hard photon radiation is not included.…”
Section: Eγ → Ezmentioning
confidence: 99%
“…However, hard photon radiation is not included. Following [163] we have compared our results with those of the code by requiring a cut on the forward-backward direction such that the integration over the scattering angle is over 10…”
Section: Eγ → Ezmentioning
confidence: 99%
“…We should give a second thought to results of Lee, Quigg, Thacker, Weldon, Chanowitz, Gaillard, Gounaris, Kögerler, Neufeld, Denner, Dittmaier, Hahn et al [6], [7] and look if there is some clue concerning the above listed questions. Maybe lattice simulations can help in the study of the transition to M = 0.…”
Section: Open Problemsmentioning
confidence: 97%